Ketergantungan Nikotin dan hubungannya dengan Perceive Stres selama Pandemi - Ryansyah, Irgie Catur; Setyaningrum, Dyah Ayu Woro (Fakultas Kedokteran Universitas Trisakti, 2023)
Background The development of COVID-19, which continues to increase in Indonesia, impacts the Indonesian people and causes stress due to the impact of the COVID-19 pandemic. Prior studies in several countries have shown that stress affects smokers during the COVID-19 pandemic. It affects smokers in two different ways, either they increase smoking or decrease smoking. This study aimed to determine the effect of Nicotine, smoking history, and changes in smoking habits during the COVID-19 pandemic on stress in smokers. Methods We conducted an online survey among active smokers in one of the villages in the South Lampung district, Indonesia November 2020 (n = 150). The survey includes sex, marital status, age of smoking initiation, duration as a smoker, changes in smoking frequency, questionnaire for nicotine dependence (the Fagerstrom Test for Nicotine Dependence questionnaire) and The Perceived Stress Scale (PSS). Data were analyzed with Chi-square<0.05). Results The results showed that the PSS score had a significant association with changes in smoking frequency (p=0.004) and nicotine dependence (p=0.001). Conclusions The study concluded that variations in nicotine dependence and changing smoking habits impacted perceived stress in smokers during the pandemic. There is a significant relationship between age at starting to smoke, number of cigarettes per day, duration of smoking habits, degree of smoking habits, and changes in smoking habits with stress levels in smokers in the COVID-19 pandemic era, and there is no relationship between types of cigarettes consumed, and stress levels in smokers in COVID-19 pandemic era.